Burkitt’s Lymphoma In Africa, A Review Of The Epidemiology And Etiology - Orem, Jackson; Mbidde, Edward Katongole; Lambert, Bo; Sanjose, Silvia de; Weiderpass, Elisabete (African health sciences, 2007)
Burkitt\'s lymphoma (BL) was first described in Eastern Africa, initially thought to be a sarcoma of the jaw. Shortly it became well known that this was a distinct form of Non Hodgkin\'s lymphoma.The disease has given insight in all aspects of cancer research and care. Its peculiar epidemiology has led to the discovery of Epstein Barr virus (EBV) and its importance in the cause of several viral illnesses and malignancies.The highest incidence and mortality rates of BL are seen in Eastern Africa. BL affects mainly children, and boys are more susceptible than girls. Evidence for a causal relationship between EBV and BL in the endemic form is fairly strong. Frequency of association between EBV and BL varies between different patient groups and different parts of the world. EBV may play a role in the pathogenesis of BL by deregulation of the oncogene c-MYC by chromosomal translocation.Although several studies suggest an association between malaria and BL, there has never been a conclusive population study in support of a direct role of malaria in causation of BL.The emergence of HIV and a distinct subtype of BL in HIV infected have brought a new dimension to the disease particularly in areas where both HIV and BL are endemic. BL has been reported as a common neoplasmin HIV infected patients, but not in other forms of immuno-depression, and the occurrence of BL seems to be higher amongst HIV positive adults, while the evidence of an association amongst children is still disputed.The role of other possible risk factors such as low socio-economical status, exposure to a plant species common in Africa called Euphorbiaceae, exposure to pesticies and to other infections such as schistosomiasis and arbovirus (an RNA virus transmitted by insect vectors) remain to be elucidated.